Nurturing Creativity in the Classroom 2010
DOI: 10.1017/cbo9780511781629.004
|View full text |Cite
|
Sign up to set email alerts
|

Developing Creative Productivity in Young People through the Pursuit of Ideal Acts of Learning

Abstract: joseph s. renzulli and catharina f. de wet introduction The September 2007 issue of Smithsonian Magazine was dedicated to "America's Young Innovators in the Arts and Sciences"-37 people under the age of 36 who are making names for themselves and are well on their way to eminence in their fields. Most of them can trace their passion and career focus to a few key experiences. Cristián Samper, for example, Acting Secretary of the Smithsonian Institution, says in his editorial introduction, My own love of science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…One of the emergent ideas was the fact that teachers who got their students to become deeply interested in a subject made the most difference. Renzulli and De Wet (2010) argued that selection of teachers could be more important than training the teachers because certain characteristics such as openness to experience, flexibility, nonauthoritative personality, optimism and high energy are the "starting material" and these are hard to cultivate with training. When we apply this to the concept of teacher efficacy, all of such factors are more about teachers' personal qualities rather than external factors.…”
Section: Discussionmentioning
confidence: 99%
“…One of the emergent ideas was the fact that teachers who got their students to become deeply interested in a subject made the most difference. Renzulli and De Wet (2010) argued that selection of teachers could be more important than training the teachers because certain characteristics such as openness to experience, flexibility, nonauthoritative personality, optimism and high energy are the "starting material" and these are hard to cultivate with training. When we apply this to the concept of teacher efficacy, all of such factors are more about teachers' personal qualities rather than external factors.…”
Section: Discussionmentioning
confidence: 99%
“…The model aims at enriching learning and teaching can be applied systematically for students of all ages (Sawyer, 2012: 393;Garcia-Cepero, 2008). The three types of enrichment are depicted in Figure. 2 (Renzulli & De Wet, 2010;39). Type I enrichment consists of general exploratory experiences that are designed to expose students to topics in areas of study not usually covered in the regular curriculum.…”
Section: Development and Enhancement Of Creativitymentioning
confidence: 99%
“…Using the Enrichment Triad Model as an intervention with twice exceptional students has also shown positive outcomes (Baum et al, 2014). Longitudinal research on the use of the Triad Model has shown that students who completed Type III projects, both in and out of school, maintained interests and career aspirations in college and in graduate school (Delcourt, 1993;Renzulli and De Wet, 2010;Westberg, 2010). Research on the use of the Triad Model in college has also been conducted, with positive findings related to student creative productivity and engagement (Brandon et al, in review).…”
Section: Journal For the Education Of The Giftedmentioning
confidence: 99%